Features of a Developing Mathematics Professional Learning Community and Affordances for Teacher Learning Opportunities - Million Chauraya; Patrick Barmby (Indonesian Journal Of Educational Research and Review, 2022)
Professional learning communities are commonly as a viable model for on-going and productive teacher learning. However few studies have investigated how such communities develop to become fully functional and sustainable learning communities. This study investigated features of a developing teacher professional learning community and opportunities for learning. Five mathematics teachers in one township primary school in South Africa and the two authors of this paper constituted the professional learning community. Transcripts of the audio-recorded meetings constituted the data analysed in this paper.  Data analysis was done using the critical incidence approach. The findings indicate that the teachers shifted from passive to more active participants. They gradually perceived themselves as a community, sharing thinking and co-creating new meanings collaboratively. The facilitators’ roles gradually shifted from leading and intervening and probing. Opportunities for learning were created with respect to knowledge of learners’ problem solving needs, and specific instructional practices to address those needs. The findings indicate that the development of effective and sustainable professional learning communities is a gradual process that takes time, and involves shifts in roles by both facilitators and teachers.